Factors Associated with Early Marriage in Sleman, Yogyakarta - Nurul Husna; Argyo Demartoto; Supriyadi Hari Respati (Masters Program in Public Health, Sebelas Maret University, 2016)
Background: Early marriageis a complex social issue with indirect implication on the quality of family. Early marriage can indirectly contribute to increasing maternal mortality rate and infant mortality rate. There were 135 early marriage cases reported in Sleman district in 2013, 150 cases in 2014, and 123 cases in 2015. The purpose of this study was to analyze factors associates with the incident of early marriage in Sleman, Yogyakarta.Subjects and Method: This was an analytic observational study with case control design conducted in Sleman, Yogyakarta, Central Java, in Indonesia, August to November 2016.A total sample of 120 study subjects consisting of 40 early married young couples and 80 in time married young couples, was selected for this study, by purposive sampling. The dependent variable was early marriage. The indipendent variables included family disharmony, emotional insecurity, promiscuity tendency, unintended pregnancy, maternal education, family social economic class, parent perception of early marriage, and local culture regarding early marriage. The data were collected by questionnaire and document review at the office of religious affairs. The data were analyzed by path analysis using STATA 13.Results: There were direct relationships between unintended pregnancy (b= 3.40; CI95%= 1.08–5.71; p=0.004), income (b=-1.58; CI95%=0.58 sd 2.18; p= 0.001), promiscuity tendency (b=1.93; CI95%=-3.11–0.06; p=0.042), parent perception of early marriage (b=2.75; CI95%=0.49-5.02; p=0.017), local culture regarding early marriage (b=5.62; CI95%=2.63–8.62; p<0.001) and the incidence of early marriage. There were indirect relationsh e. ips between family disharmony, emotional security, promiscuity tendency, maternal education, and incident of early marriage.Conclusion: There were direct relationships between unintended pregnancy, social economic class, promiscuity tendency, parent perception of early marriage, local culture regarding early marriage and the incidence of early marriage.Keywords: Early marriage, family disharmony, unintended early married, local culturCorrespondence: Nurul Husna. Masters Program in Public Health, Sebelas Maret University, Surakarta.Journal of Health Promotion and Behavior (2016), 1(2): 87-98https://doi.org/10.26911/thejhpb.2016.01.02.04